The effect of controlled pressure adjustment in an urban water distribution system on household demand - Meyer, Niel; Heinz Erasmus Jacobs; Westman, Trevor; McKenzie, Ronnie (Journal of water supply : research and technology - AQUA, 2018)
The effect of pressure adjustments on individual consumer water demand is presented in this paper. The study involved collecting and analysing data from two sites in an operational water reticulation system in South Africa. Pressures and flow rates were monitored at a few strategic locations and at 44 individual homes during a series of controlled pressure adjustments. A total of 25 weeks' data, recorded at 15-minute intervals, were analysed. The two systems were subjected to 11 pressure adjustments, lasting 2 weeks each. Results showed a positive relationship between the average pressure change and median consumer demand, where reduced pressure led to reduced consumer demand. The linear model suggested a relationship of ΔQ ≈ 0.5ΔP between the change in average pressure and the change in median consumer demand, at a consumer connection. However, notable variation from one consumer to the next was apparent. Based on night flow analysis, the on-site leakage on consumer properties (downstream of the consumer meter) represented about 25% of the total metered demand of the study sample. The field tests also confirmed that there are practical limits to the level of pressure reduction that can be attained, beyond which the consumers become unsatisfied with the pressure.